Peran Transformasi PKBM terhadap Tingkat Literasi Sosial dan Ekonomi Masyarakat Putus Sekolah di Era Digital: Studi pada PKBM Melati Kabupaten Enrekang - Hamriani; Ilham Assidiq; Saddam Ramli; Saidang; M. Hatta (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The development of digital technology encourages non-formal educational institutions to transform learning to improve the community's ability to face social and economic changes. School dropouts are a group that requires strengthening social and economic literacy to be able to utilize technology productively. This study aims to analyze the transformation of the Melati Community Learning Center (PKBM) in Enrekang Regency in improving the social and economic literacy of school dropouts and identify supporting and inhibiting factors in its implementation. This study uses a qualitative approach with a case study type conducted at the Melati Community Learning Center (PKBM) in Enrekang Regency in 2026. The research instrument was the researcher herself with data sources in the form of PKBM managers, tutors, and students through interviews, observation, and documentation techniques. Data analysis used the Miles and Huberman model through the stages of data condensation, data presentation, and drawing conclusions. Data validity was tested through triangulation of sources and techniques. The results of the study indicate that digital transformation at the Melati Community Learning Center (PKBM) was carried out through the use of WhatsApp, Zoom, Google Forms, and YouTube in learning. This transformation improved students' social literacy as indicated by increased communication, active discussions, and digital interactions. In terms of economic literacy, students are beginning to utilize social media and marketplaces to promote products and engage in simple business activities. Research implications indicate that digital transformation of community-based learning (PKBM) can be a strategy for empowering dropouts, but strengthening digital facilities and competencies is necessary for optimal implementation.